Going green from within: correlational insights into the spread of pro-environmental behavior through the lens of organismic integration theory - Molkenthin, Magdalena; Christoforakos, Lara; Hassenzahl, Marc; Laschke, Matthias (Frontiers in Psychology, 2025)
The share of private household's direct fuel use in global CO2 emissions accounts approximately 20 percent and, when indirect effects of their overall consumption are included, between 50 and 80 percent of the total resource use produced or imported by country. This underscores the importance of achieving savings through pro-environmental behavior (PEB) in all sectors of daily life, such as recycling and nutrition. As PEB is often perceived as unattractive and unexperiental, political measures using external incentives are predominantly consulted. However, these types of motivation are often short-term and context-dependent. In contrast, more internal regulated motivation not only strengthens PEB frequency but may also extend it across contexts. This occurs when the behavior aligns with personal values, is seen as personally and future-relevant, and is experienced as part of one's identity – thus helping to overcome psychological barriers in the context of environmentalism. Based on the Organismic Integration Theory (OIT), online surveys were conducted with participants from the Global North (N = 146), providing self-disclosure on their attitude toward environmentalism, their level of exposure to the negative consequences of climate change, their PEB in everyday life across various sectors and their type of regulation. The analysis confirmed all hypotheses, showing that higher internalized motivation was associated not only with more frequent PEB but also with its broader spread across different sectors of everyday life. Additionally, our findings indicate that the type of regulation according to OIT might be more closely associated with PEB than individuals' direct exposure to climate change, even though intrinsic motivation, as the highest level of regulation, may not necessarily need to be the focus in the context of environmentalism.